Physical passaging of embryoid bodies generated from human pluripotent stem cells. - Mi-Young Son; Hyun-Jin Kim; Min-Jeong Kim; Yee Sook Cho (PLoS ONE, 2011)
Spherical three-dimensional cell aggregates called embryoid bodies (EBs), have been widely used in in vitro differentiation protocols for human pluripotent stem cells including human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs). Recent studies highlight the new devices and techniques for hEB formation and expansion, but are not involved in the passaging or subculture process. Here, we provide evidence that a simple periodic passaging markedly improved hEB culture condition and thus allowed the size-controlled, mass production of human embryoid bodies (hEBs) derived from both hESCs and hiPSCs. hEBs maintained in prolonged suspension culture without passaging (>2 weeks) showed a progressive decrease in the cell growth and proliferation and increase in the apoptosis compared to 7-day-old hEBs. However, when serially passaged in suspension, hEB cell populations were significantly increased in number while maintaining the normal rates of cell proliferation and apoptosis and the differentiation potential. Uniform-sized hEBs produced by manual passaging using a 1∶4 split ratio have been successfully maintained for over 20 continuous passages. The passaging culture method of hEBs, which is simple, readily expandable, and reproducible, could be a powerful tool for improving a robust and scalable in vitro differentiation system of human pluripotent stem cells.